Influence of Learning Model Type Cooperative Scramble with Picture Media on Motivation and Students Learning Outcomes of IPS Class 2 SDN 2 Tropodo - Artiningsih, Atik; Riyanto, Yatim; Harmanto, Harmanto (Universitas Malikussaleh, 2019)
This study aims to determine the effect of the Scramble type cooperative learning model with image media on the motivation and learning outcomes of grade 2 elementary school students. This research was conducted at the SDN Tropodo 2 Waru Sidoarjo Regency 2018/2019. This type of research experiment uses a quantitative approach, with nonequivalent (pretest and posstest) design contril group design. This study uses two classes namely the experimental class and the control class. The study sample was class 2A as the experimental class and 2B as the control class. The instruments used were motivation observation sheets and learning outcomes tests. Data analysis techniques used included normality test, homogeneity test, and independent sample t-test. The results of the study showed that there was an effect oflearning model the scramble type cooperative on media images on the motivation and learning outcomes of grade 2 elementary school students.value of gain normalized Motivatedexperiment class 0.174, control class 0.115value gain normalized of student learning outcomes experimental class 0.192, control class 0.141 test results independent samples t-test motivation showed tcount of 7.845> ttable of 1,677. the results of the test of independent samples t-test of learning outcomes indicate that the value of tcount is 5.254> ttable of 1,677. It can be concluded that thelearning model scramble type cooperative with image media influences the motivation and learning outcomes of grade 2 students in elementary school.